2019
DOI: 10.1177/1059840519872785
|View full text |Cite
|
Sign up to set email alerts
|

Sex Education, Condom Access, and Contraceptive Referral in U.S. High Schools

Abstract: In the United States, sex education in schools varies significantly across districts. Many schools operate without state-guided health education curricula, leaving decisions up to individual districts. The purpose of this study was to explore what type of sex education is being offered in U.S. high schools in addition to assessing the frequency of condom access and contraceptive referral. A total of 772 high school superintendents were surveyed with a response rate of 40.4% ( n = 297). Data show most districts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our findings were similar to national trends indicating that the number of schools that provide sexuality education is declining (Santelli et al, 2017). In a recent study of geographically representative high schools, 63% of high schools reported that they teach comprehensive sexuality education, yet only 7% had condoms available on campus and over 70% did not make referrals for contraception (Maziarz et al, 2019). Our findings also align with statewide trends showing few schools in Texas offer any health education, no sexuality education, or are likely to provide abstinence-only education (Texas Campaign to Prevent Teen Pregnancy, n.d.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to national trends indicating that the number of schools that provide sexuality education is declining (Santelli et al, 2017). In a recent study of geographically representative high schools, 63% of high schools reported that they teach comprehensive sexuality education, yet only 7% had condoms available on campus and over 70% did not make referrals for contraception (Maziarz et al, 2019). Our findings also align with statewide trends showing few schools in Texas offer any health education, no sexuality education, or are likely to provide abstinence-only education (Texas Campaign to Prevent Teen Pregnancy, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive sexuality education programs have been shown to reduce sexual risk behaviors and delay sexual intercourse (Santelli et al, 2017). However, the amount and type of sexuality education and services offered in schools vary significantly across the United States (Maziarz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Evidence shows that comprehensive sex education, which includes education on contraception, is the most effective form of sex education. 4,[10][11][12][13] The World Health Organization defines comprehensive sexuality education as "accurate, ageappropriate information about sexuality and their sexual and reproductive health". 14 There is no current federal mandate on sex education in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among schools that provide sex education within the United States, many provide abstinence-only sex education, which is proven to be less effective. 4,[10][11][12][13] This bias toward abstinence-only sex education is evident in federal funding for sex education. For example, states that receive federal funding from the government through Title V State Sexual Risk Avoidance Education, the largest source of federal funding for sex education funded at 75 million dollars per year, "cannot include demonstrations, simulations, or distribution of contraceptive devices".…”
Section: Introductionmentioning
confidence: 99%